Flexible torque control for wind turbines considering frequency response under wind speed crossing region - Wang, Yingwei; Guo, Yufeng; Du, Yilin; Xu, Weimao (Frontiers in Energy Research, 2023)
The operational range of a wind turbine is typically divided into two regions based on wind speed: below and above the rated wind speed. The turbine switches between these two regions depending on the prevailing wind speed; however, during the transition, the generator may undergo transient shocks in torque, which can negatively impact both the mechanical load of the turbine and the reliability of the power system. This article presents a flexible torque control method for wind turbines, specifically designed to handle the transition between wind speed regions when the turbine is participating in frequency regulation. First, the anomalies in generator torque caused by traditional torque control methods during frequency response scenarios are analyzed. Next, two methods—dynamic deloading and flexible torque control—are developed to address these issues. The developed methods set transition regions based on generator speed, which helps to reduce the impact of transient changes in generator torque. Importantly, the addition of transition regions does not require additional feedback, making the controller easy to implement. The response characteristics of the proposed methods are then analyzed under different deloading factors and wind speeds using model linearization. Simulation studies are presented to verify the effectiveness of the proposed methods. Overall, this study demonstrates the potential value of flexible torque control methods for wind turbines, which can help to mitigate the negative impact of torque shocks and improve the reliability and efficiency of wind power systems.